Association Between Age and Cholesterol, Blood Sugar, and Uric Acid Levels in Office Workers - Darwis Darwis; Fikitri Marya Sari; Ade Sissca Villia; Ade Febryanti; Nehru Nugroho (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Degenerative conditions related to cholesterol, blood sugar, and uric acid tend to increase with age and lifestyle changes, particularly among office workers in the productive age group. This study investigates the association between age and levels of cholesterol, blood sugar, and uric acid among employees of the Bengkulu Ministry of Health Polytechnic. A descriptive analytical design was employed using medical check-up data from 203 respondents. Data normality was assessed using the Kolmogorov-Smirnov test, and correlations were analyzed using Pearson's method. The findings revealed significant correlations between age and total cholesterol, HDL, LDL, triglycerides, blood sugar, and uric acid levels, although most correlations were weak in strength. These results suggest that age contributes to elevated biochemical markers associated with degenerative diseases, highlighting the importance of routine health monitoring among office workers as a strategy for early prevention. Keywords: Cholesterol, blood sugar, uric acid, degenerative diseases, office workers